Brucella aortitis managed with debridement, extra-anatomical bypass, and long-term antimicrobial therapy. (February 2023) - Perry, John; Alslaim, Hossam; Agarwal, Gautam
Objectives: This report aims to review the management and outcomes of Brucella -associated mycotic aortic aneurysms. Methods: This is a retrospective chart review at a tertiary-level healthcare system. IRB approval was waived per policy. Results: We describe a case of Brucella aortitis acquired from habitual contact with wild hogs. Clinical presentation included lower back pain and elevated white blood cell count. Diagnosis was confirmed with imaging showing an infrarenal abdominal aortic aneurysm and serology revealing elevated Brucella antibodies titers. The patient was initially managed with endovascular aortic repair and combined oral and intravenous antibiotics therapy. He then underwent explanation and extra-anatomical bypass due to symptomatic periaortic infection and interval development of type I endoleak. The patient was asymptomatic after his final operation at 24 months of follow-up and remained on suppressive oral antibiotic therapy. Conclusions: An aortic aneurysm secondary to Brucella is a rare entity. A detailed history of long-term exposure to animals may be a clue to obtain serologic testing. Operative debridement and re-establishing of reliable blood flow combined with long-term antibiotic suppression are the mainstay of treatment.